MONITORING OF BOVINE LEUKEMIA VIRUS IN KAZAKHSTAN: ANALYSIS OF SEROLOGICAL AND MOLECULAR DIAGNOSTIC METHODS (Experimental biology, 2025)
Bovine leukemia virus (BLV) poses a significant threat to livestock farming in Kazakhstan. This study presents a comprehensive analysis of the prevalence of BLV based on data from 2024, obtained using serological and molecular diagnostic methods. The sensitivity and specificity of agar gel immunodiffusion (AGID), enzyme-linked immunosorbent assay (ELISA), and real-time polymerase chain reaction (RT-PCR) were evaluated. Serological methods demonstrated a high seroprevalence of BLV among animals, with ELISA showing greater sensitivity compared to AGID, confirmed by statistically significant results (p < 0.05). RT-PCR identified fewer active infections, indicating the latent nature of the disease in many infected animals. The correlation coefficient between AGID and RT-PCR was 0.791 (p = 0.011), indicating a high degree of concordance between these methods. However, the correlation between ELISA and RT-PCR was weaker (r = 0.461, p = 0.212), highlighting the difference in the diagnostic nature of these tests. ...
Keywords: bovine leukemia virus, serological methods, RT-PCR, monitoring, Kazakhstan.